Global Supply Chain Pressure and 3D Printing Investments - Bunyaratavej, Kraiwinee (STIE Malangkucecwara, 2025)
Recent events such as the pandemic have shed some light on the vulnerability of the global supply chains when they are greatly disrupted. Some firms opt to increase their in-house capacity, while some businesses resort to sourcing locally. Technology, which had been used to increase efficiency of firms, became even more important in solving and preventing supply chain risks by increasing flexibility in sourcing. 3D printing has played an important role in relieving some of the pressure from businesses. Hence, businesses might not have to choose between improving efficiency by producing or sourcing where it is cheap versus improving security by sourcing or bringing facilities closer to home. In this paper, the aim is to shed some light on the impact of global supply chain problems on investments into 3D printing start-ups. Using a Poisson regression model for investigating the hypotheses, we found that as pressure has built on the supply chains, businesses made more investments in the 3D printing technology in order to navigate through the volatility. The future research could expand to cover more technology and time period. We hope that the paper will highlight the importance of 3D printing technology in businesses when supply chain disruption occurs